Hamiltonian flow in Coulomb gauge Yang-Mills theory - Leder, Markus; Pawlowski, Jan M. (Arxiv, 2010)
We derive a new functional renormalization group equation for Hamiltonian Yang-Mills theory in Coulomb gauge. The flow equations for the static gluon and ghost propagators are solved under the assumption of ghost dominance within different diagrammatic approximations. The results are compared to those obtained in the variational approach and the reliability of the approximations is discussed.